Operational Considerations for Collective Licensing Frameworks in the Music Publishing Industry - Kim, Lidia (The Columbia Journal of Law & the Arts, 2025)
A large part of my work is to negotiate and issue blanket music publishing licenses that cover the availability for use of full catalogs of music on behalf of the songwriters and rightsholders my company represents. It should not come as a surprise if I were to say that licensing negotiations often center around what is the appropriate value for the use of music (i.e., ample consideration for the rights granted under contract), and that the economics of a deal take the spotlight. After all, the goal is to get music professionals paid for their work. However, equally important to the success of a deal, and therefore a key component of negotiating a blanket license, is operational—how is the use of music managed, and what are the responsibilities of each of the contracting parties to administer the license and pay the underlying rightsholders. Administering an individual synch license is straightforward—the licensee knows what music will be used and how and relays that to licensor, licensor issues the license, collects payment, and administers the royalties. The thought exercise becomes more complicated with digital service providers (DSPs) whose services and platforms host and make available seemingly limitless quantities of music, where the volume of usage is high or the extent of usage unknowable (or both).